Evaluation the Effect of Different Antioxidants Applied After Bleaching on Teeth Color Stability - Degirmenci, Alperen; Kara, Emine; Unalan Degirmenci, Beyza; Ozcan, Mutlu (Brazilian Dental Science, 2020)
Objective: Vital bleaching is popular treatment option for discolored teeth. But at post-treatment stage, loss of adhesion is highly reported. Literature focused on antioxidant application for the answer of this issue. The aim of this study is comparing effects of six different antioxidants on color stability of bleached teeth. Material and Methods: This study includes total of 84 extracted intact non-carious lower incisors. 35% hydrogen peroxide was applied on the labial surfaces of specimens in accordance with manufacturer's instructions. The bleached teeth were divided into 7 groups. No antioxidants were applied to the control group. For the experimental groups, the following antioxidants were applied for 10 minutes each: 5% proanthocyanidin, 5% sodium ascorbate, 5% lycopene, %5 green tea, %5 white tea and %5 ?-tocopherol. CIE L*, a* and b* values of the teeth were measured by a spectrophotometer. The data were analyzed using IBM SPSS version 23. Results: The differences between the groups were determined with one-way ANOVA. The one-way ANOVA test revealed a statistically significant difference between the groups (p